The inextricable scene: global temporalities in Dorothee Elmiger’s Aus der Zuckerfabrik - Jürjens, Kira (Journal for German and Scandinavian Studies / Списание „Германистика и скандинавистика“, 2026)
Drawing on the example of Dorothee Elmiger’s Aus der Zuckerfabrik (2020), the article examines how the abundance of space and time of global world contexts can be converted into literary form. While the experimental novel does not present the complexity of the world in the order of linear narratives and rather aims to exhibit its complex network character, the book follows literary-aesthetic principles of meaning production that can be related to the globalisation narratives of poetic realism. The article focusses on four different temporal configurations and literary formal principles that are important for the text: 1) The staging of simultaneity as a narrative problem and potential, 2) sugar as a hyperlink, 3) the significant moment and 4) repetition.
Keywords: time; realism; globalization; contemporary literature